The challenges of learning programming subject in online distance learning (ODL) environment at UiTM Pahang / Nor Zalina Ismail and Mohd Rizal Razak - Ismail, Nor Zalina; Razak, Mohd Rizal (Universiti Teknologi MARA Cawangan Pahang, 2021)
The outbreak of COVID-19 pandemic worldwide, including in Malaysia since early 2020 until now has shifted education activities from face-to-face to online environments. Teaching and learning programming subjects are also not exempted from using online distance learning (ODL) mode. Programming is challenging to learn in a face-to-face environment, and even more so in an ODL environment. This subject requires problem-solving skills, high motivation, and high self-directed learning to complete the programming tasks given by lecturers. This study aims to investigate the UiTM Pahang students' perception on the challenges of learning programming and their feelings (i.e., motivation and isolation) when learning programming in the ODL mode. In order to achieve the objectives of the study, a questionnaire was distributed to students undertaking three diploma courses at UiTM Pahang. The responses of 303 students who took programming in the ODL mode were analysed using SPSS statistical software. The findings show that 74.3% of the students perceive that it is more difficult to learn programming in the ODL mode than face-to-face. In terms of the students’ feelings, 67% of the students feel demotivated, and 69% feel isolated when learning programming in the ODL mode. The output of this study is an indication for the programming educators to develop more effective teaching methods or techniques in teaching programming subjects in the ODL mode.